Pericytes’ Circadian Clock Affects Endothelial Cells’ Synchronization and Angiogenesis in a 3D Tissue Engineered Scaffold - Mastrullo, Valeria; van der Veen, Daan R.; Gupta, Priyanka; Matos, Rolando S.; Johnston, Jonathan D.; McVey, John H.; Madeddu, Paolo; Velliou, Eirini G.; Campagnolo, Paola (Frontiers in Pharmacology, 2022)
Angiogenesis, the formation of new capillaries from existing ones, is a fundamental process in regenerative medicine and tissue engineering. While it is known to be affected by circadian rhythms in vivo, its peripheral regulation within the vasculature and the role it performs in regulating the interplay between vascular cells have not yet been investigated. Peripheral clocks within the vasculature have been described in the endothelium and in smooth muscle cells. However, to date, scarce evidence has been presented regarding pericytes, a perivascular cell population deeply involved in the regulation of angiogenesis and vessel maturation, as well as endothelial function and homeostasis. More crucially, pericytes are also a promising source of cells for cell therapy and tissue engineering. Here, we established that human primary pericytes express key circadian genes and proteins in a rhythmic fashion, upon synchronization. Conversely, we did not detect the same patterns in cultured endothelial cells. In line with these results, pericytes’ viability was disproportionately affected by circadian cycle disruption, as compared to endothelial cells. Interestingly, endothelial cells’ rhythm could be induced following exposure to synchronized pericytes in a contact co-culture. We propose that this mechanism could be linked to the altered release/uptake pattern of lactate, a known mediator of cell-cell interaction which was specifically altered in pericytes by the knockout of the key circadian regulator Bmal1. In an angiogenesis assay, the maturation of vessel-like structures was affected only when both endothelial cells and pericytes did not express Bmal1, indicating some compensation system. In a 3D tissue engineering scaffold, a synchronized clock supported a more structured organization of cells around the scaffold pores, and a maturation of vascular structures. Our results demonstrate that pericytes play a critical role in regulating the circadian rhythms in endothelial cells, and that silencing this system disproportionately affect their pro-angiogenic function. In particular in the context of tissue engineering and regenerative medicine, considering the effect of circadian rhythms may be critical for the development of mature vascular structures and to obtain the maximal reparative effect.